Τουριστική Ήπειρος : σελίδες τουρισμού, λογοτεχνίας, ιστορίας - Μάλαμας, Λάμπρος, 1928-2012 ([χ.ό.], 2001)
Κεφάλαια -- Ήπειρος: Γιάννινα,Κάστρο, Νησί, Παμβώτιδα, Σπήλαιο, Δωδώνη, Γραμμένο, Ζίτσα, Αρτα, Πρέβεζα, Πάργα, Μέτσοβο, Βίκος, Καλπάκι, Κόνιτσα, Ηγουμενίτσα, Παραμυθιά